On-demand reconstitutable hyaluronic acid-doped azathioprine microcrystals effectively ameliorate ulcerative colitis via selective accumulation in inflamed tissues. (30th September 2022) - Lee, Juho; Oshi, Murtada A.; Kwak, Dongmin; Kim, Hyunwoo; Kim, Jihyun; Hlaing, Shwe Phyu; Saparbayeva, Aruzhan; Hwang, Seonghwan; Jung, Yunjin; Yoo, Jin-Wook
Abstract : On-demand reconstitutable hyaluronic acid-doped azathioprine microcrystals showed enhanced therapeutic effects via colitis tissue-selective delivery of azathioprine. Abstract : Although CD44-targeted delivery of pure drug microcrystals of azathioprine (AZA) could be a desirable approach to treat ulcerative colitis (UC), premature drug release and systemic absorption before reaching the colitis region remain a major obstacle. In this study, to overcome these limitations, we developed on-demand reconstitutable HA-doped AZA microcrystals (EFS/HA-AZAs) via incorporating hyaluronic acid (HA)-doped AZA microcrystals (HA-AZAs) into a Eudragit FS (EFS) microcomposite. Since EFS acts as a protective layer, the premature release of AZA in the simulated conditions of the stomach and small intestine was substantially reduced, while HA-AZAs were successfully reconstituted from the EFS/HA-AZAs in the colonic environment, resulting from the pH-triggered dissolution of EFS. After complete reconstitution of HA-AZAs in the colon, HA-AZAs selectively accumulated in the inflamed region via the HA-CD44 interaction. Owing to successful colitis-targeted delivery, EFS/HA-AZAs showed potent anti-inflammatory effects in a dextran sulfate sodium-induced murine colitis model within 7 days without systemic toxicity. These results suggest that EFS/HA-AZAs could be a promising drug delivery system for UC treatment.